3° Encuentro del Mercosur Ampliado. Máquinas y Herramientas para la Agricultura Familiar. Tecnologías apropiadas, memoria e investigación - Palioff Nosal, Claudia Alejandra (Comp.); Gornitzky, Cora Miriam (Comp.) (Ediciones INTA, 2025)
The creation of a space dedicated to the promotion of Appropriate Technologies had its founding stone in Puerto Tirol, Chaco. Today, five years after those significant events, we are holding a new Meeting on Machines and Tools for Family Farming of the Expanded Mercosur. A meeting that, year after year, consolidates a space for institutional and technological innovation with the participation of farmers, local entrepreneurs, workshop leaders, and SMEs from across the country. This meeting is both public and private, and various state institutions and funding entities join in. The Proceedings presented here describe what happened during the 3rd Meeting, which took place in November 2012 at the AMBA Experimental Station in the Buenos Aires municipality of Ituzaingó, in the Buenos Aires Metropolitan Area, a region with the greatest development of urban and peri-urban agriculture in the country. The imprint of labor-intensive production, with a tendency toward environmentally friendly production methods, allowed visitors to the area to come into contact with technologies and developments from other provinces that were unavailable on the local market.